Digital Marketing Tips on Instagram (Case Study on Madu Modow Honey SME) - Elvi Lastriani; Mira Rosmala; David Opel Alexander; Muhammad Hafiz Abd Rashid; Amiral Arief Absy; Dian Syah Putri (Eastasouth Journal of Effective Community Services, 2025)
This Community Service (PKM) activity was conducted by STIE Dharma Putra at the Madu Madow Honey MSME in Siak Regency, Riau, in June 2025. This MSME produces premium-quality Sialang Siak Honey but faces challenges in digital marketing and preparing simple financial reports. The activity's title was "Simple Digital Marketing Tips on Instagram (Case Study of the Madu Modow Honey MSME)." The goal was to provide training and mentoring so that MSMEs could implement effective digital marketing strategies through Instagram to expand market reach and increase sales. Furthermore, the training also included preparing simple financial reports for better business management. The resulting output was improved digital skills and optimization of the MSME's Instagram account. The expected outcomes were increased market reach, increased sales turnover, and increased brand awareness of Madu Sialang Siak. This activity involved four lecturers and ten students, with the output being a National Journal.